Counting - Sirett, Dawn; Calver, Susan; Harvey, Victoria (London Dorling Kindersley Limited, 2013)
Introduces your baby to numbers with touch and feel textures. This title helps them touch and learn about numbers one to ten with a cuddly dog, furry cats, shiny fire engines, fuzzy ducklings and more
Picture books
1 2 13 23
Keywords: Picture book for children